Strategies for Compliance with Non-Binding International Decisions: The Spanish Case - Montesinos Padilla, Carmen; Gómez Fernández, Itziar (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2021)
The Spanish State is among the countries with high standards of compliance with its international obligations on human rights. Regardless of the reasons that explain the respect for such commitments, it is surprising to note that the degree of compliance differs depending on the international guarantee mechanism. Compliance with treaties whose oversights is attributed to a court, such as the European Court of Human Rights, is stricter than compliance with covenants under the United Nations, whose supervision is recognised to the committee established by each treaty or by their annexed protocols. Even though the Committees also respond to individual complaints raised by persons subject to the Spanish State jurisdiction, the binding nature of their resolutions is questioned by some State institutions. Both members of the executive and the judiciary. This paper analyses the grounds that justify this two-speed compliance and questions the institutional arguments that support such reality. Our reflection insists that the obligations derived from all human rights treaties ratified by Spain are identical and demand an equal response from the State institutions. The international human rights law and the Spanish Constitution itself so require it.